Utilizations of fiber Bragg gratings and Fabry-Perot lasers for fast wavelength switching technique - Yeh, CH; Chi, S (My University, 2005)
A novel tunable laser structure, based on Fabry-Perot lasers and fiber Bragg gratings with self-seeding operation, is proposed and experimentally investigated. The wavelength tuning can be obtained by properly adjusting the bias currents of FP lasers. The response time of wavelength switching of < 6.8 ns, a 3.38 mn tuning range, and a side-mode suppression ratio of > 23 dB have been achieved experimentally, This proposed tunable laser has the advantages of simple architecture, potentially low cost, data direct modulation and fast wavelength switching. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Fabry-Perot; optical switching; SMSR; WDM